2012
DOI: 10.1177/070674371205700304
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Mental Health Stigma Questions: The Importance of Social Desirability and Data Collection Method

Abstract: Objective:To evaluate the impact on the general public of England's Time to Change program to reduce mental health-related stigma and discrimination using newly developed measures of knowledge and intended behaviour regarding people with mental health problems, and an established attitudes scale, and to investigate whether social desirability affects responses to the new measures and test whether this varies according to data collection method. Method:The Mental Health Knowledge Schedule (MAKS) and Reported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 26 publications
0
91
1
1
Order By: Relevance
“…Second, responses assessing attitudes might be affected by social desirability. However, using a self-complete method for measuring attitudes toward people with mental health problems is less prone to social desirability bias than faceto-face interview [52] and we opted for this method in our study. This is not to say that a social desirability bias was eliminated completely, vice versa, its role should be carefully considered when interpreting the findings of our study as medical doctors could be more compelled to respond in line with perceived societal expectations than members of the general population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Second, responses assessing attitudes might be affected by social desirability. However, using a self-complete method for measuring attitudes toward people with mental health problems is less prone to social desirability bias than faceto-face interview [52] and we opted for this method in our study. This is not to say that a social desirability bias was eliminated completely, vice versa, its role should be carefully considered when interpreting the findings of our study as medical doctors could be more compelled to respond in line with perceived societal expectations than members of the general population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…An assessment conducted immediately after the campaign launched found that fewer people said that they had often or very often worried that others would view them unfavorably because they use mental health services (Schneider, Beeley, and Repper, 2011). Although not a direct measure of stigma, Henderson, Evans-Lacko, et al (2012) assessed whether people with mental illness experienced more or less discrimination in a range of 21 life behaviors (e.g., from their employers, neighbors, landlords). Twelve months after the campaign launched, respondents reported significantly less discriminatory behavior in about one-third of the life behaviors-specifically, they reported fewer instances of being shunned and fewer instances of being discriminated against because of their mental illness by friends, family, social acquaintances, and employers .…”
Section: Multimedia Campaignsmentioning
confidence: 99%
“…It is likely that some of the differences may be due to cultural and economic changes over the last decades (Anderson, Chisholm, & Fuhr, 2009), and to possible differences in the respondents' own perceptions and interpretations of the survey questions. Also, surveys may underestimate actual drinking behaviors and MHS due to social desirability and fear of stigma (Henderson, Evans-Lacko, Flach, & Thornicroft, 2012;Stockwell et al, 2004). Furthermore, the Ugandan sample was smaller than that for Nigeria, which could have led to finding fewer significant associations.…”
Section: Discussionmentioning
confidence: 98%